2017
DOI: 10.1002/asna.201613139
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of the historic Yemeni reports of supernova SN 1006: Early discovery in mid‐April 1006?

Abstract: The recently published Yemeni observation report about SN 1006 from al‐Yamānī clearly gives AD 1006 April 17 ± 2 (mid‐Rajab 396h) as the first observation date. Since this is ∼1.5 weeks earlier than the otherwise earliest reports (April 28 or 30) as discussed so far, we were motivated to investigate an early sighting in more depth. We searched for additional evidences from other areas like East Asia and Europe. We found that the date given by al‐Yamānī is fully consistent with other evidence, including the fol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…We will now consider four more presumable aurorae listed in table 2 of H+15 (Chinese text in our Figure ), somewhat related to each other, which were previously discussed in Neuhäuser et al (): there are two entries for AD 1006 Apr 14 (brackets are our additions, but as meant in H+15): 1006 Apr 14 R[ed] V[apour] n[orth] [in] Kaifeng [lunar phase] 0.46 and 1006 Apr 14 W[hite] V[apour] near the moon [in] Kaifeng [lunar phase] 0.46 (0.46 means near full moon). One of the two texts is from the astronomical treatise ( Tianwen zhi ) of the Song Shi , and the other from its treatise on general omenology ( wuxing zhi ).…”
Section: Comments On Recent Searches For Aurorae and Sunspots From DImentioning
confidence: 99%
See 2 more Smart Citations
“…We will now consider four more presumable aurorae listed in table 2 of H+15 (Chinese text in our Figure ), somewhat related to each other, which were previously discussed in Neuhäuser et al (): there are two entries for AD 1006 Apr 14 (brackets are our additions, but as meant in H+15): 1006 Apr 14 R[ed] V[apour] n[orth] [in] Kaifeng [lunar phase] 0.46 and 1006 Apr 14 W[hite] V[apour] near the moon [in] Kaifeng [lunar phase] 0.46 (0.46 means near full moon). One of the two texts is from the astronomical treatise ( Tianwen zhi ) of the Song Shi , and the other from its treatise on general omenology ( wuxing zhi ).…”
Section: Comments On Recent Searches For Aurorae and Sunspots From DImentioning
confidence: 99%
“…There is another instance of the same phrase ( yellow vapor like a pillar penetrated the moon ) dated to the fourth month of the third year of the Tianxi reign period (AD 1019) given without the guimao date—even though there is a guimao date in that month (AD 1019 Mar 23, close to full moon on May 21/22). It is possible that the event somehow got transposed to the wrong reign period (Neuhäuser et al ).…”
Section: Comments On Recent Searches For Aurorae and Sunspots From DImentioning
confidence: 99%
See 1 more Smart Citation
“…Connections of historical transients with SNe or novae are problematic in particular due to difficulties in the understanding of historical texts, which could be improved by transdisciplinary collaboration between astrophysicists, philologists, and historians—such a project is undertaken by us since 2012 under the name of Terra‐Astronomy (see Neuhäuser et al 2020). We have already studied various phenomena, for example, historical SNe (new Arabic records of SN 1006 in Rada & Neuhäuser 2015 and Neuhäuser et al 2017a, 2017b as well as of SNe 1572 and 1604 in R. Neuhäuser et al 2016b), comets in the late 8th century (e.g. Chapman et al 2014, 2015), and reconstruction of solar activity around AD 775 from aurorae and radiocarbon (e.g.…”
Section: Introduction: Historical Novae and Supernovaementioning
confidence: 99%
“…A recent review on historical SNe is found in Stephenson & Green (2002); a few additional Arabic language records of SNe 1006, 1572, and 1604 are collected in Rada & R. , R. Neuhäuser et al (2016Neuhäuser et al ( , 2017a, and R. Neuhäuser, Ehrig-Eggert & Kunitzsch (2017b). Recent work on historical 'guest stars' including novae and SNe can be found in Stephenson & Green (2005, 2009, a cometography in Kronk (1999), a critical collection of Chinese records of 'broom ' and 'fuzzy stars' in Pankenier, Xu & Jiang (2008, henceforth P+08) -all ignored in HVP20 and HV20a,b.…”
Section: Introductionmentioning
confidence: 99%